2013
DOI: 10.1002/chir.22200
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Virtual Spectrometer for Chiroptical Spectroscopies: The Case of Nicotine

Abstract: The impressive advances of computational spectroscopy in most recent years are providing robust and user-friendly multifrequency virtual spectrometers, which can also be used by nonspecialists to complement experimental studies. At the heart of these developments there are latest-generation models based on Density Functional Theory for the proper treatment of stereo-electronic effects, coupled to the polarizable continuum model to deal with bulk solvent effects, and low-order perturbative treatments of anharmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 58 publications
0
34
0
Order By: Relevance
“…In line with previous work of some of the present authors, [28][29][30][31][32][33] we aim to develop accurate yet user-friendly strategies for the calculation of RROA spectra of complex systems, also interacting with external complex environments. Here, we start our investigation on such a field, by addressing the problem of origin invariance in RROA, a fundamental topic which, to the best our knowledge, has never been directly addressed.…”
Section: Introductionmentioning
confidence: 73%
“…In line with previous work of some of the present authors, [28][29][30][31][32][33] we aim to develop accurate yet user-friendly strategies for the calculation of RROA spectra of complex systems, also interacting with external complex environments. Here, we start our investigation on such a field, by addressing the problem of origin invariance in RROA, a fundamental topic which, to the best our knowledge, has never been directly addressed.…”
Section: Introductionmentioning
confidence: 73%
“…In particular, the first test case concerns a rigid small molecule, methyloxirane in aqueous solution, which has been reported to be particularly challenging for continuum solvent methodologies. The second example refers to a flexible molecule of medium size, nicotine, again in aqueous solution, which has as well been taken as reference for testing the performance of continuum solvation models . For each case, the comparison between the QM/FQ/PCM and both experimental data and continuum solvation approaches is proposed, the latter to especially evidence the role of short‐range specific interactions with respect to long‐range bulk effects.…”
Section: Some Selected Examplesmentioning
confidence: 99%
“…Also, it has been amply demonstrated that the presence of the external environment may affect not only the absolute value but also especially the sign of the chiroptical response . Therefore, the use of either the most accurate levels of calculations may be ineffective if not accompanied by reliable methodologies to take into account environmental effects …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fully ab initio VPT2 88 approach allows also inclusion of non-specific solvent effects by means of the polarizable continuum model (PCM) essentially without any additional cost 91 , and has been also extended to take into account non-equilibrium solvent effects on vibrational (e.g. IR or VCD) transition intensities [92][93][94] .…”
Section: Introductionmentioning
confidence: 99%